The effectiveness of public administration in Kazakhstan (Journal of Economic Research & Business Administration, 2015)
This article discusses issues such as the value of the public service , the need to rapidly enhance the effectivenessefficiency of public administration and the quality of services , the problem of the fight against corruption .
Keywords: public administration; the fight against corruption